Machinability parameters of single-tooth and multi-tooth face milling - Kovač, Pavel (Journal of Production Engineering, 1994)
Because of the higher amount of material waste, most tool life tests in the face milling process are done with a single-tooth tool and the results are used for mufti-tooth tool life prediction. The total tool life of a multi-tooth cutter by multiplying the values of tool life of a single tooth cutter by number of teeth, is obtained But there the phenomenon of tool life reduction in the case of multi-tooth cutter in comparison with single tooth cutter , during constant cutting conditions was observed. The later experimental investigations carried out in milling showed that the phenomenon of run-out of the cutting edges in milling cutter yield influence on the tool life of cutter, surface roughness, cutting forces and cutting temperature.